2017
DOI: 10.1111/jce.13286
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological relation between the superior vena cava and right superior pulmonary vein in patients with paroxysmal atrial fibrillation

Abstract: An electrophysiological interrelation may be present between the SVC and RSPV in patients with paroxysmal AF. Semiempiric SVC isolation limited to patients with an arrhythmogenic RSPV may be a more efficient treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Previous histological examination in autopsy specimens has shown that PV myocardial sleeves were found in 100% of patients with AF, compared to 85% of patients without AF [30]. The recent studies from voltage map showed that the lengths of myocardial sleeves are longer in the left and right superior PVs but markedly shorter in the left and right inferior PVs [31,32]. Patients with AF have significant longer myocardial sleeves [30].…”
Section: Distinct Electrophysiological and Structural Characteristmentioning
confidence: 99%
“…Previous histological examination in autopsy specimens has shown that PV myocardial sleeves were found in 100% of patients with AF, compared to 85% of patients without AF [30]. The recent studies from voltage map showed that the lengths of myocardial sleeves are longer in the left and right superior PVs but markedly shorter in the left and right inferior PVs [31,32]. Patients with AF have significant longer myocardial sleeves [30].…”
Section: Distinct Electrophysiological and Structural Characteristmentioning
confidence: 99%
“…Currently, race and ethnicity and their stratified outcomes are rarely reported in the AF ablation literature, perpetuating this knowledge gap. Investigations of adjunctive lesion sets in homogenous populations by race or ethnicity that demonstrate incremental benefit may not generalize, contributing to reproducibility issues in the field …”
Section: Discussionmentioning
confidence: 99%
“…Investigations of adjunctive lesion sets in homogenous populations by race or ethnicity that demonstrate incremental benefit may not generalize, contributing to reproducibility issues in the field. 18,19 Prior worldwide surveys on AF ablation methods, efficacy, and safety found minimal variation in procedure success rates by geographic region. [1][2][3] However, these surveys are no longer contemporary, rely on proceduralists' self-reported outcomes, do not report country-level data, and do not investigate the effect on outcomes of powerful determinants of reported procedure success (e.g., followup protocols).…”
Section: Incidence Of Af Is Lower In Asians and Africans As Compared Tomentioning
confidence: 99%
“…Thereafter, a cavotricuspid isthmus line was created, with an endpoint of bidirectional conduction block [ 7 ]. If non-PV ectopies were reproducibly observed with and without the continuous infusion of isoproterenol (1–4 mcg/min), they were targeted for ablation [ 13 , 14 , 15 , 16 , 17 ]. Neither ablation of continuous fractionated atrial electrograms nor left atrial linear ablation was performed in this series in the index procedures.…”
Section: Methodsmentioning
confidence: 99%